3
$\begingroup$

Let $A$ and $B$ be two matrices. Then, $$ \|e^{A+B}- e^A\| \leq \|B\|e^{\|A\|+\|B\|}. $$

Can anyone give me a proof or reference for this inequality, please? Thank you.

$\endgroup$
3
$\begingroup$

Yes, this is mostly just combinatorial and algebraic identities.

Letting $f(0)=A$ and $f(1)=B$, we can distribute terms to get $$(A+B)^n-A^n = \sum_{\sigma\in\{0,1\}^n \\ \;\;\sigma \not\equiv 0} \prod_{j=1}^n f(\sigma(j))$$ Thus \begin{align*}\|(A+B)^n-A^n\| &\leq \sum_{\sigma\in\{0,1\}^n \\ \;\;\sigma \not\equiv 0} \prod_{j=1}^n \|f(\sigma(j))\| \\&= \sum_{k=1}^n {{n}\choose {k}} \|A\|^k \|B\|^{n-k} \\ &= (\|A\|+\|B\|)^n - \|A\|^n \\ &= \|B\| \bigg( \sum_{j=0}^{n-1} (\|A\|+\|B\|)^{n-j-1}\|A\|^{j}\bigg) \\ &\leq n\cdot \|B\| \cdot (\|A\|+\|B\|)^{n-1}\end{align*} In the second line we just used basic combinatorics, in the third line we used the binomial theorem, in the fourth line we used the identity $x^n-y^n = (x-y)\big(\sum_{0}^{n-1} x^jy^{n-1-j}\big)$, and in the last line we just used the fact that $\|A\|^j \leq (\|A\|+\|B\|)^j$ for all $j$.

Therefore \begin{align*} \|e^{A+B}-e^{A}\| &\leq \sum_{n=1}^{\infty} \frac{\| (A+B)^n -A^n\|}{n!} \\ &\leq \sum_{n=1}^{\infty} \frac{n \cdot \|B\| \cdot (\|A\|+\|B\|)^{n-1}}{n!} \\ &= \|B\|\sum_{n=0}^{\infty} \frac{(\| A\|+\|B\|)^n}{n!} \\ &= \|B\|e^{\|A\|+\|B\|} \end{align*} This proves the claim. One could also use more advanced methods like Frechet calculus to prove even stronger bounds than this, like $\|e^{B}-e^{A}\| \leq \|B-A\|e^{\max \{\|A\|,\|B\|\}},$ or even better if $A,B$ are symmetric then $\|e^{B}-e^{A}\| \leq \|B-A\|e^{\max \Sigma(A) \cup \Sigma(B)}$.

$\endgroup$
  • $\begingroup$ Where can I read about these inequalities? $\endgroup$ – Swapnil Tripathi May 22 '19 at 4:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.